2011
DOI: 10.1371/journal.pone.0026148
|View full text |Cite
|
Sign up to set email alerts
|

A Potent Inhibitor of SIK2, 3, 3′, 7-Trihydroxy-4′-Methoxyflavon (4′-O-Methylfisetin), Promotes Melanogenesis in B16F10 Melanoma Cells

Abstract: Flavonoids, which are plant polyphenols, are now widely used in supplements and cosmetics. Here, we report that 4′-methylflavonoids are potent inducers of melanogenesis in B16F10 melanoma cells and in mice. We recently identified salt inducible kinase 2 (SIK2) as an inhibitor of melanogenesis via the suppression of the cAMP-response element binding protein (CREB)-specific coactivator 1 (TORC1). Using an in vitro kinase assay targeting SIK2, we identified fisetin as a candidate inhibitor, possibly being capable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 42 publications
(51 reference statements)
0
24
0
Order By: Relevance
“…Whereas methoxy flavones do competitively inhibit tyrosinase, their application in cosmetic or medicinal products that aim to decrease tyrosine or dopamine oxidation should be treated with caution. Experiments with murine B16/F10 melanoma cells have shown that treatment with polyhydroxy flavones results in reduced melanogenesis 45,46 but that polymethoxy flavones affect cell signalling, and induce tyrosinase expression and melanogenesis. [45][46][47][48][49][50][51][52] However, similar experiments with humans rather than murine melanocytes have shown that polymethoxy flavones inhibit the induction of melanogenesis.…”
Section: Molecular Docking To Mushroom Tyrosinasementioning
confidence: 99%
“…Whereas methoxy flavones do competitively inhibit tyrosinase, their application in cosmetic or medicinal products that aim to decrease tyrosine or dopamine oxidation should be treated with caution. Experiments with murine B16/F10 melanoma cells have shown that treatment with polyhydroxy flavones results in reduced melanogenesis 45,46 but that polymethoxy flavones affect cell signalling, and induce tyrosinase expression and melanogenesis. [45][46][47][48][49][50][51][52] However, similar experiments with humans rather than murine melanocytes have shown that polymethoxy flavones inhibit the induction of melanogenesis.…”
Section: Molecular Docking To Mushroom Tyrosinasementioning
confidence: 99%
“…SIK2 has been implicated in various signaling cascades such as glucose and fat metabolism in the liver, neuroprotective effect in the brain, and the eumelanin synthetic pathway in melanocytes (34)(35)(36)(37)(38). To invariably delineate the functional consequences of the chronic depletion of SIK2 in vivo, we generated knockout mice for SIK2 by deleting two critical exons (exons 2 and 3) from the genomic sequences, resulting in .90% depletion of SIK2 in most tissues as confirmed by quantitative PCR and Western blot analysis (Fig.…”
Section: Sik2 Ko Mice Are Mildly Glucose and Insulin Intolerant But Dmentioning
confidence: 99%
“…Furthermore, SIK2 is known to regulate the initiation of mitosis through phosphorylating the centrosome linker protein, C-Nap1 (5). An intimate link between SIK2 and the CREB coactivator TORC1/2 has also been established, particularly in the contexts of melanogenesis (6,7), cerebral ischemia-associated neuronal survival (8), and corticotropin-releasing hormone transcription (9). However, as an AMPK family kinase, its possible functional link to cellular stress response has not been reported and requires further clarification.…”
Section: Salt-inducible Kinase 2 (Sik2)mentioning
confidence: 99%